1991
DOI: 10.4098/at.arch.91-28
|View full text |Cite
|
Sign up to set email alerts
|

Conspecific recognition and mating in stone marten Martes foina

Abstract: Conspecific recognition and mating in stone marten Martes foinaThierry LODE Lodé T. 1991. Conspecific recognition and mating in stone marten Martes foina. Acta theriol. 36: 275 -283.The study of the mating of the stone marten Martes foina (Erxleben, 1777) revealed the importance of behavioural modifications which favour the intraspecific tolerance. The precopulatory activities affected the whole mode of communication. The frequencies of the male's olfactory investigation of the female's anogenital region and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…All observed copulations occurred between 07.10 and 11.00 h. The durations of two of these copulations were accurately recorded and were 5 and 14.5 min, respectively. This represents a copulatory act of much shorter duration than previously described for pine martens (Strickland et al 1982, Strickland andDouglas 1987), stone martens (Lode 1991) and mustelids in general, but longer than the copulatory acts of free-ranging pine martens described by Henry and Raphael (1989). Conditions of confinement may have contributed to these dif ferences among studies.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…All observed copulations occurred between 07.10 and 11.00 h. The durations of two of these copulations were accurately recorded and were 5 and 14.5 min, respectively. This represents a copulatory act of much shorter duration than previously described for pine martens (Strickland et al 1982, Strickland andDouglas 1987), stone martens (Lode 1991) and mustelids in general, but longer than the copulatory acts of free-ranging pine martens described by Henry and Raphael (1989). Conditions of confinement may have contributed to these dif ferences among studies.…”
Section: Resultsmentioning
confidence: 56%
“…The call appeared to be lower in pitch and of longer duration than the nervous chuckle used by martens when frightened. This vocalization is probably the "love call" identified for pine martens by Adams (1962) and Strickland et al (1982) and may be analogous to the "muted cluck" described by Lode (1991) for stone martens. Lode (1991) suggested that this vocalization may function to reduce conspecific ag gression in order to facilitate copulation.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations